Towards a Model of Corporate and Social Stakeholder Engagement: Analyzing the Relations Between a French Mutual Bank and Its Members - Girard, Carine; Sobczak, André (2012)
The aim of this article is to develop a new classification of stakeholders based on the concept of corporate and social engagement. Engagement is analyzed as an organizational learning process between the managers of an organization and its stakeholders. It is a necessary condition to improve the organization’s impact on its economic, social, and natural environment. Applied to the membership of a French mutual bank in order to identify the members’ varying levels of engagement, this new mapping technique may help managers to adapt their practices to the degree of engagement of each identified group of members, and to modify their financial products and communications to foster engagement among as many of these groups as possible.
Keywords: Mutual banks; Corporate Social Responsibility; Corporate engagement; Stakeholder engagement